Efficacy of Citalopram on Acute Ischemic Stroke Outcome: A Randomized Clinical Trial. (July 2017) - Savadi Oskouie, Daryoush; Sharifipour, Ehsan; Sadeghi Bazargani, Homayoun; Hashemilar, Mazyar; Nikanfar, Masoud; Ghazanfari Amlashi, Saeed; Abbaszade, Zahra; Sadeghihokmabadi, Elyar; Rikhtegar, Reza; Golzari, Samad E. J.
Background and purpose . Ischemic stroke (IS) is one of the main causes of death and disability in the adult population, and recovery from it is a major health concern worldwide. The aim of the present study was to evaluate the effectiveness of citalopram on 3-mounth outcome of nondepressed acute IS patients. Methods . In a randomized, placebo-controlled clinical trial, 144 patients with acute IS were studied for 3 months. In one group, the patients received oral citalopram 20 mg (once daily), and in the other group, they received placebo. All patients received standard care, including physiotherapy. Patients with depression were excluded throughout the study. The primary outcome of the study was set to a 50% reduction in the 3-month National Institutes of Health Stroke Scale compared with the baseline scores (Clinical Trial Registration URL:http://www.irct.ir ; Unique identifier: IRCT201203192150N2). Results. The mean age of patients was 66.4 years. Of 144 eligible patients, 15 patients died (4 in the citalopram and 11 in the placebo group), and 21 patients did not complete the study follow-up period (10 in the citalopram and 11 in the placebo group). The primary outcome of the study was achieved in 57 patients (79%) in the citalopram and 39 patients (54%) in the placebo group ( P < .001), with risk ratio and number needed to treat of 2 (CI = 1.2-3) and 4 (CI = 2.5-8.6), respectively. No major adverse events were found in either group. Conclusions. Citalopram is a safe and tolerable medication in patients with acute IS, which could improve the outcome in these patients.